O sushchnost' sportivnoi formy - Zhelyaskov, T. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper is to discuss the problem of the sports form in the context of the new ideas about its essence, nature and practical sense. The author considers some discussional questions connected with professor L.P. Matveyev's definition of the sports form. He attempts to analyse the problem from the system approach position. The author defines the sports form as such a state of an athlete's special working capacity, when all factors the sports achievement are situated In their optimal meanings and correlations (socalled concordance), ensuring the maximal realization of the athlete's motor potential in the corresponding motor activities (sports result).